A capacitor-based power equivalent model for salinity-gradient osmotic energy conversion. (15th December 2021) - Liu, Q.; Tang, Z.T.; Qu, Z.G.; Ren, Qinlong; Zhang, J.F.; Tang, R.X.
Highlights: An unsteady model is proposed for osmotic energy conversion. The variation of salt concentration during actual operation is considered. The accuracy of model is verified by salinity-gradient power generation experiments. A parallel encapsulation method is provided to enhance output power density. Abstract: Converting the salinity-gradient into electricity via ion migration in nanoconfined channels driven by the salt concentration gap between sea and river water is an important renewable energy utilization method. The osmotic energy conversion device is regarded as a power source with constant voltage output in the conventional constant voltage source (V-source) power equivalent circuit model, which is based on a steady state with constant concentration on both sides of the membrane. In this study, an unsteady equivalent capacitor–capacitor/resistor (C-CR) power equivalent circuit model is proposed to consider the salt concentration variation during actual operation. The maximum relative deviation of the calculated short circuit current between the C-CR power equivalent circuit model and the measured experimental data is 7.06%. The maximum relative deviation of the predicted maximum output power density between the C-CR power equivalent circuit model and the measured experimental data is less than 14.22%, while the corresponding maximum deviation for the V-source power equivalent circuit model has an error of 38.14%. A parallel encapsulation method by embedding graphene oxide membranes (GOMs) into polydimethylsiloxane (PDMS) is provided to offer an extended accessible area for ion transport to enhance the ion flux and output power density. This method reveals a linearly increased output power with the number of GOMs, which provides convenience for increasing output power. This work provides an effective way to design integrated osmotic energy conversion devices, which promotes the development of salinity-gradient-driven energy conversion systems.